PERBANDINGAN FORECASTING MENGGUNAKAN METODE SINGLE DAN DOUBLE EXPONENTIAL SMOOTHING PADA PENJUALAN ROTI (Studi kasus Elud Cake and Bakery) - Danang Dhivari; Banly Aguchino; Paduloh (CV. Adiba Aisha Amira, 2024)
Bread is a food that is very popular with Indonesian people because it is very high in fiber, making people who consume it feel full for a long time and eat small portions. Forecasting is the process of compiling previous information to obtain new information. This research uses Single and Double Exponential Smoothing forecasting methods with a case study, namely bread. A comparison will be made between these two methods to find out the best method for forecasting. The results of this research show that the Single Exponential Smoothing method is the best to use because it has results with an SSE of 7,116,359,819, when compared with Double Exponential Smoothing of 7,469,741,265.